(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence, patterns, and related factors of sleep disturbances using the Sleep-50 scale in patients with bipolar disorder (BD) during a current depressive episode receiving treatment at the National Institute of Mental Health. Subjects and methods: A cross-sectional descriptive study was conducted on 123 patients diagnosed with bipolar affective disorder in a current depressive episode according to ICD-10 criteria from January 2025 to October 2025. Results: Based on the Sleep-50, sleep disturbances were identified in 80.5% of patients. The most prevalent domains were insomnia (84,8%), narcolepsy/hypersomnolence (24,2%) nightmares (20,2%), restless legs/periodic limb movements (9,1%), obstructive sleep apnea (7,1%), and circadian rhythm disorder (4,0%). Among those with insomnia, difficulty initiating sleep (82,1%), difficulty maintaining sleep (66,7%), and early morning awakening (29,8%) were reported. Mean total sleep time was 5,9 ± 1,7 h/night while time in bed averaged 8,7 ± 1,5 h, with poor/very poor sleep efficiency in 75,8% of patients. Significant correlates of sleep disturbance were age ≥ 40 years (OR = 3,04; 95% CI: 1,14–8,09; p = 0,023) and ≥3 hospitalizations (OR = 12,63; 95% CI: 4,18–38,10; p < 0,001). Conclusion: Sleep disturbances are highly prevalent in patients with bipolar depression, with insomnia predominating and marked deficits in sleep efficiency. Older age and greater illness burden (multiple hospitalizations) are key correlates. These findings support the need for routine assessment of sleep problems in patients with bipolar depression.